Advances in Phosphasilene Chemistry. Issue 50 (30th June 2017) - Nesterov, Vitaly; Breit, Nora C.; Inoue, Shigeyoshi
Abstract: Heavier alkene analogues possess unique electronic properties and reactivity, encouraging multidisciplinary research groups to utilize them in the rational design of novel classes of compounds and materials. Phosphasilenes are heavier imine analogues, containing highly reactive Si=P double bonds. Recent achievements in this field are closely related to the progress in the chemistry of stable low‐coordinate silicon compounds. In this Review, we have attempted to summarize in a comprehensive way the available data on the structures, syntheses, electronic and chemical properties of these compounds, with an emphasis on recent achievements. Abstract : Doubly bonded neighbors : phosphasilenes are heavier imine analogues, containing very reactive Si=P double bonds. This Review summarizes structures, syntheses, electronic, and chemical properties of these and related species with an emphasis on recent achievements.